2013
DOI: 10.3109/0886022x.2013.844622
|View full text |Cite
|
Sign up to set email alerts
|

Febuxostat for treating allopurinol-resistant hyperuricemia in patients with chronic kidney disease

Abstract: Background: Availability of the novel xanthine oxidase inhibitor febuxostat, which has multiple excretion pathways, enables investigation of the significance of serum uric acid control on renal function in patients with chronic kidney disease (CKD). Methods: This was an exploratory, retrospective, observational study conducted at a single Japanese center. Serum uric acid concentrations and serum creatinine levels in the 6 months before and after the start of febuxostat treatment were collected for CKD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
5
23
1
1
Order By: Relevance
“…Thus, renal function should be regularly monitored during drug treatment for ensuring safety. No serious adverse reaction occurred during the study, which is similar to the finding in previous study using febuxostat in severe CKD patients (Sircar et al, 2015;Saag et al, 2016;Hira et al, 2015;Juge et al, 2017;Shibagaki et al, 2014;Sakai et al, 2014). The results indicate the safety of febuxostat use in CKD patients.…”
Section: Safetysupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, renal function should be regularly monitored during drug treatment for ensuring safety. No serious adverse reaction occurred during the study, which is similar to the finding in previous study using febuxostat in severe CKD patients (Sircar et al, 2015;Saag et al, 2016;Hira et al, 2015;Juge et al, 2017;Shibagaki et al, 2014;Sakai et al, 2014). The results indicate the safety of febuxostat use in CKD patients.…”
Section: Safetysupporting
confidence: 79%
“…However, previous information on the efficacy and safety of febuxostat use in CKD patients above stage 3 is limited. Several studies explored the efficacy and safety of using febuxostat for treating patients undergoing advanced CKD treatment (Table 5) (Sircar et al, 2015;Saag et al, 2016;Hira et al, 2015;Juge et al, 2017;Shibagaki et al, 2014;Sakai et al, 2014). However, because of the limited number of patients included in this study and lower dosages used, further research is required for verifying the results.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies reported a beneficial effect of UA lowering on CKD progression and UA has been proposed as a promising target of therapy in CKD patients. [37][38][39][40][41][42][43] Recently, Omori et al 37 reported that in animal models with obstructive nephropathy, febuxostat inhibited renal interstitial inflammation and fibrosis suggesting a therapeutic value in slowing CKD progression. In accordance, Sakai et al 42 reported that febuxostat by lowering UA levels in CKD patients may suppress the progression of CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Another study also reported the usefulness of febuxostat in elderly patients with renal impairment [13] . Several studies have suggested that sustained urate-lowering therapy with febuxostat may impede renal decline in patients with gout [14,15] . However, the administration of febuxostat to patients with severe renal dysfunction (CCr <30 ml/min) or to those undergoing maintenance hemodialysis (HD) has not been examined in sufficient detail and is information that is clinically desired [16] .…”
Section: Population Pharmacokinetics and Therapeutic Efficacy Of Febumentioning
confidence: 99%